Where truth lies - TVE International (Ace communications, 1990)
Gideon Niewoudt-nicknamed 'Notorious Niewoudt'-was one of the fearing security police in S.Africa's former arpatheid government.He and his colleagues are responsible for torture,poisoning,death of numerous black activist..